2010
DOI: 10.1093/brain/awq332
|View full text |Cite
|
Sign up to set email alerts
|

Resting oscillatory cortico-subthalamic connectivity in patients with Parkinson’s disease

Abstract: Both phenotype and treatment response vary in patients with Parkinson's disease. Anatomical and functional imaging studies suggest that individual symptoms may represent malfunction of different segregated networks running in parallel through the basal ganglia. In this study, we use a newly described, electrophysiological method to describe cortico-subthalamic networks in humans. We performed combined magnetoencephalographic and subthalamic local field potential recordings in thirteen patients with Parkinson's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
379
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(433 citation statements)
references
References 68 publications
41
379
3
2
Order By: Relevance
“…Importantly, the whole network is already known to support executive functions [63,64]. The pattern of anatomical and functional connectivity of these non-motor regions of the cortex with the non-motor regions of the STN is compatible with a possible influence of executive origin of the former on the latter via the hyperdirect pathway [65][66][67][68]. Besides, the fact that non-motor territories of the STN are connected to the motor ventrolateral thalamus [65] strongly suggests that the STN may, indeed, act as a direct interface between executive and motor systems.…”
Section: Relevance To the Pathophysiology Of Akinesiamentioning
confidence: 86%
“…Importantly, the whole network is already known to support executive functions [63,64]. The pattern of anatomical and functional connectivity of these non-motor regions of the cortex with the non-motor regions of the STN is compatible with a possible influence of executive origin of the former on the latter via the hyperdirect pathway [65][66][67][68]. Besides, the fact that non-motor territories of the STN are connected to the motor ventrolateral thalamus [65] strongly suggests that the STN may, indeed, act as a direct interface between executive and motor systems.…”
Section: Relevance To the Pathophysiology Of Akinesiamentioning
confidence: 86%
“…Although the above studies focus on oscillations within the BG, it has been argued that this activity is more likely to be generated externally, as a part of the thalamo-cortical loop [26], [27], [25] and maintain its coherence throughout the BG.…”
Section: B Oscillations and Pdmentioning
confidence: 99%
“…Simultaneous recordings using MEG and local field potentials in the subthalamic nucleus (STN) reveal that and activities are coupled to temporal brain areas and are involved in a functional separation of basal ganglia-cortex loops with different frequency patterns (Hirschmann et al, 2011). Litvak et al (2011) reported that in PD patients at rest, -range activities are coupled with temporoparietalbrainstem areas while -range activities are coupled with the frontal network. Thus, it is likely that -range oscillations might correlate with the motor loop and with manifestations of akinesia and rigidity.…”
Section: Magnetoencephalography (Meg)mentioning
confidence: 99%